Drosophila functional screening of de novo variants in autism uncovers damaging variants and facilitates discovery of rare neurodevelopmental diseases - Marcogliese, Paul C.; Deal, Samantha L.; Andrews, Jonathan; Harnish, J. Michael; Bhavana, V. Hemanjani; Graves, Hillary K.; Jangam, Sharayu; Luo, Xi; Liu, Ning; Bei, Danqing; Chao, Yu-Hsin; Hull, Brooke; et al. (Cell reports (Cambridge), 2022)
Individuals with autism spectrum disorder (ASD) exhibit an increased burden of de novo mutations (DNMs) in a broadening range of genes. While these studies have implicated hundreds of genes in ASD pathogenesis, which DNMs cause functional consequences in vivo remains unclear. We functionally test the effects of ASD missense DNMs using Drosophila through “humanization” rescue and overexpression-based strategies. We examine 79 ASD variants in 74 genes identified in the Simons Simplex Collection and find 38% of them to cause functional alterations. Moreover, we identify GLRA2 as the cause of a spectrum of neurodevelopmental phenotypes beyond ASD in 13 previously undiagnosed subjects. Functional characterization of variants in ASD candidate genes points to conserved neurobiological mechanisms and facilitates gene discovery for rare neurodevelopmental diseases. [Display omitted] •We generate and characterize >300 (TG4 and cDNA) Drosophila mutants and transgenics•Humanization and overexpression strategies to functionally assess ASD variants in vivo•ASD variant data in flies help identify GLRA2-related neurodevelopmental disorders•Basic and clinical collaboration facilitates variant testing and disease gene discovery Marcogliese et al. generate >300 Drosophila mutants and use complementary rescue-based and overexpression approaches to study the function of de novo missense variants found in autism. They find that 38% of missense changes have functional consequences and identify variants in GLRA2 that cause a variable neurological disorder.